Method for detoxifying chrome corundum and producing refractory brick
By crushing chromium corundum, leaching hexavalent chromium and adding binding agents, chromium corundum refractory bricks are prepared, which solves the problem of environmental pollution of chromium corundum and improves the quality and corrosion resistance of refractory bricks.
Patent Information
- Application Number
- CN202411988316.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The hexavalent chromium present in chromium corundum is environmentally contaminated and difficult to deal with safely, and the prior art is difficult to effectively remove and convert it into an environmentally friendly refractory material.
Chromium corundum is crushed and free hexavalent chromium is leaching, and then bonding agents such as molten zirconium mullite and phosphoric acid are added. After stirring, pressing and sintering at high temperature, chromium corundum refractory bricks are prepared.
The environmentally friendly treatment of chromium corundum is realized, the quality and corrosion resistance of refractory bricks are improved, and the performance of refractory bricks is further improved through modification and the addition of nanomaterials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and more specifically, relates to a method for detoxifying chrome corundum and producing refractory bricks. Background Art
[0002] Chrome corundum is an excellent high-temperature refractory material. Its high-temperature resistance and corrosion resistance are irreplaceable by traditional alumina and magnesium oxide materials. At the same time, chrome corundum refractory materials are irreplaceable in many industries that require refractory materials.
[0003] However, due to the presence of a small amount of toxic and harmful hexavalent chromium in chrome corundum, it is easy to pollute the environment. According to the latest national hazardous waste management system requirements, chrome corundum is classified as hazardous waste. Now a technical solution is needed to harmlessly treat chrome corundum and convert it into usable materials to ensure that chrome corundum has more environmentally friendly and safe properties. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these purposes and other advantages according to the present invention, a method for detoxifying chrome corundum and producing refractory bricks is provided, comprising:
[0006] Step 1, crushing the chrome corundum into different specifications, and then placing it in a leaching solution to leach free hexavalent chromium, filtering, washing, and drying the soaked chrome corundum to obtain detoxified chrome corundum;
[0007] Step 2: adding fused zirconium mullite and a binder of phosphoric acid to the detoxified chrome corundum, stirring and mixing, leaving for a period of time, adding a binder of aluminum dihydrogen phosphate, mixing, and pressing to form a block of chrome corundum;
[0008] Step 3: Sintering the pressed block of chrome corundum at high temperature to obtain chrome corundum refractory bricks.
[0009] Preferably, in the step 1, the chrome corundum is crushed to a particle size of 5 to 1 mm and 100 to 400 meshes.
[0010] Preferably, in step 1, the leaching solution is one of a reducing agent, water or an acid, the reducing agent can be hydrazine hydrate, and the acid can be one or more of nitric acid, hydrochloric acid and sulfuric acid.
[0011] Preferably, in step 1, the leaching process is: taking a reducing agent or water or acid at room temperature, adding chrome corundum thereto at a mass ratio of 1:1, and leaving it for 24 hours to leach free hexavalent chromium.
[0012] Preferably, in the step 2, the mass ratio of chrome corundum to fused zirconium mullite is 4-16:1, and the amount of phosphoric acid added as a binder is 2.5%-5% of the total mass of the chrome corundum and the fused zirconium mullite.
[0013] Preferably, in step 2, the particle size of the fused zirconium mullite is 0 to 3 mm.
[0014] Preferably, in step three, the amount of the binder aluminum dihydrogen phosphate added is 1% to 2.5% of the total mass of chrome corundum, fused zirconium mullite and binder phosphoric acid.
[0015] Preferably, in step three, the high temperature sintering temperature is 1400° C. to 1600° C., and the sintering time is 20 h to 25 h.
[0016] Preferably, before step 2, the detoxified chrome corundum is first modified by:
[0017] S1. Immerse the detoxified chrome corundum in a mixed acid of 3% nitric acid and 2% hydrofluoric acid, soak it at 15-30°C for 5-10 minutes, then take out the detoxified chrome corundum, wash it, and dry it;
[0018] S2, soaking the dried detoxified chrome corundum in 40g / L tin chloride acid solution at room temperature for 8-16min, then taking out the detoxified chrome corundum, placing it in an acetone solution for ultrasonic cleaning, and drying;
[0019] S3, soaking the dried detoxification chrome corundum in 0.15g / L palladium chloride acid solution, soaking at 40-50°C for 8-16min, then taking out the detoxification chrome corundum, washing and drying;
[0020] S4, soak the dried detoxified chrome corundum in a chemical plating solution, the chemical plating solution includes 8g / LNiSO4, 30g / L, 15g / L CH3COONa, 25g / L sodium citrate, 8ml / L lactic acid, soak at 80-90°C for 30-45min, take it out after soaking, and obtain the modified detoxified chrome corundum with nickel plating on the surface.
[0021] Preferably, after the detoxified chrome corundum is modified, 4-6% of the mass of the detoxified chrome corundum is additionally added with nano hexagonal boron nitride and nano silicon dioxide in step 2, and the mass ratio of nano hexagonal boron nitride to nano silicon dioxide is 2:1.
[0022] The present invention has at least the following beneficial effects:
[0023] (1) The present invention improves the quality of chrome corundum by detoxifying chrome corundum through reducing agent, water and acid leaching, thereby obtaining more environmentally friendly chrome corundum, thereby making the quality of refractory bricks higher;
[0024] (2) The present invention can process chrome corundum in an efficient and low-cost manner, converting chrome corundum into high-value and high-performance refractory bricks to achieve its maximum economic value;
[0025] (3) The present invention also improves the corrosion resistance of chrome corundum refractory bricks by modifying the chrome corundum and adding nano hexagonal boron nitride and nano silicon dioxide before calcination.
[0026] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0027] The present invention is described in further detail below so that those skilled in the art can implement it according to the description.
[0028] Example 1
[0029] A method for detoxifying chrome corundum and producing refractory bricks, comprising:
[0030] Step 1, crushing 100 kg of chrome corundum into particles with a particle size of 3 mm, then adding the chrome corundum particles into 100 kg of water, soaking and placing for 24 hours to leach free hexavalent chromium, filtering, washing and drying the soaked chrome corundum to obtain detoxified chrome corundum;
[0031] Step 2: Add 25 kg of fused zirconium mullite with a particle size of 2 mm to the detoxified chrome corundum, then add 3.125 kg of phosphoric acid, stir evenly and place for 6 hours, then add 1.28 kg of aluminum dihydrogen phosphate for mixing, and press to form block chrome corundum.
[0032] Step 3: sinter the pressed block chrome corundum in a high temperature furnace at 1400° C. for 24 hours to obtain chrome corundum refractory bricks.
[0033] Example 2
[0034] A method for detoxifying chrome corundum and producing refractory bricks, comprising:
[0035] Step 1, crushing 100 kg of chrome corundum into particles with a particle size of 2 mm, then adding the chrome corundum particles into 100 kg of hydrazine hydrate, soaking and placing for 24 hours to leach free hexavalent chromium, filtering, washing and drying the soaked chrome corundum to obtain detoxified chrome corundum;
[0036] Step 2: Add 6.25 kg of fused zirconium mullite with a particle size of 2 mm to the detoxified chrome corundum, then add 3.187 kg of phosphoric acid, stir evenly and let stand for 6 hours, then add 1.09 kg of aluminum dihydrogen phosphate for mixing, and press into block chrome corundum.
[0037] Step 3: sinter the pressed block chrome corundum in a high temperature furnace at 1500° C. for 23 hours to obtain chrome corundum refractory bricks.
[0038] Example 3
[0039] A method for detoxifying chrome corundum and producing refractory bricks, comprising:
[0040] Step 1, crushing 100 kg of chrome corundum into particles with a particle size of 4 mm, then adding the chrome corundum particles into 100 kg of 30% hydrochloric acid, soaking and placing for 24 hours to leach free hexavalent chromium, filtering, washing and drying the soaked chrome corundum to obtain detoxified chrome corundum;
[0041] Step 2: Add 6.25 kg of fused zirconium mullite with a particle size of 2 mm to the detoxified chrome corundum, then add 4.25 kg of phosphoric acid, stir evenly and let stand for 6 hours, then add 2.21 kg of aluminum dihydrogen phosphate for mixing, and press into block chrome corundum.
[0042] Step 3: sinter the pressed block chrome corundum in a high temperature furnace at 1600° C. for 24 hours to obtain chrome corundum refractory bricks.
[0043] Example 4
[0044] Step 1, crushing 100 kg of chrome corundum into particles with a particle size of 3 mm, then adding the chrome corundum particles into 100 kg of water, soaking and placing for 24 hours to leach free hexavalent chromium, filtering, washing and drying the soaked chrome corundum to obtain detoxified chrome corundum;
[0045] Before step 2, the detoxified chrome corundum is modified by:
[0046] S1. Immerse the detoxified chrome corundum in a mixed acid of 3% nitric acid and 2% hydrofluoric acid, soak it at 15-30°C for 5-10 minutes, then take out the detoxified chrome corundum, wash it, and dry it;
[0047] S2, soaking the dried detoxified chrome corundum in 40g / L tin chloride acid solution at room temperature for 8-16min, then taking out the detoxified chrome corundum, placing it in an acetone solution for ultrasonic cleaning, and drying;
[0048] S3, soaking the dried detoxification chrome corundum in 0.15g / L palladium chloride acid solution, soaking at 40-50°C for 8-16min, then taking out the detoxification chrome corundum, washing and drying;
[0049] S4, soak the dried detoxified chrome corundum in a chemical plating solution, the chemical plating solution includes 8g / LNiSO4, 30g / L, 15g / L CH3COONa, 25g / L sodium citrate, 8ml / L lactic acid, soak at 80-90°C for 30-45min, take it out after soaking, and obtain the modified detoxified chrome corundum with nickel plating on the surface.
[0050] Step 2: Add 25 kg of fused zirconium mullite with a particle size of 2 mm to the modified detoxified chrome corundum with nickel plating on the surface, then add 3.125 kg of phosphoric acid, stir evenly and let stand for 6 hours, then add 1.28 kg of aluminum dihydrogen phosphate for mixing, and press into block chrome corundum.
[0051] Step 3: sinter the pressed block chrome corundum in a high temperature furnace at 1400° C. for 24 hours to obtain chrome corundum refractory bricks.
[0052] Example 5
[0053] Step 1, crushing 100 kg of chrome corundum into particles with a particle size of 3 mm, then adding the chrome corundum particles into 100 kg of water, soaking and placing for 24 hours to leach free hexavalent chromium, filtering, washing and drying the soaked chrome corundum to obtain detoxified chrome corundum;
[0054] Before step 2, the detoxified chrome corundum is modified by:
[0055] S1. Immerse the detoxified chrome corundum in a mixed acid of 3% nitric acid and 2% hydrofluoric acid, soak it at 15-30°C for 5-10 minutes, then take out the detoxified chrome corundum, wash it, and dry it;
[0056] S2, soaking the dried detoxified chrome corundum in 40g / L tin chloride acid solution at room temperature for 8-16min, then taking out the detoxified chrome corundum, placing it in an acetone solution for ultrasonic cleaning, and drying;
[0057] S3, soaking the dried detoxification chrome corundum in 0.15g / L palladium chloride acid solution, soaking at 40-50°C for 8-16min, then taking out the detoxification chrome corundum, washing and drying;
[0058] S4, soak the dried detoxified chrome corundum in a chemical plating solution, the chemical plating solution includes 8g / LNiSO4, 30g / L, 15g / L CH3COONa, 25g / L sodium citrate, 8ml / L lactic acid, soak at 80-90°C for 30-45min, take it out after soaking, and obtain the modified detoxified chrome corundum with nickel plating on the surface.
[0059] Step 2: Add 25kg of fused zirconium mullite with a particle size of 2mm, 4kg of nano hexagonal boron nitride and 2kg of nano silicon dioxide to the modified detoxified chrome corundum with nickel plating on the surface, then add 3.125kg of phosphoric acid, stir evenly and let stand for 6h, then add 1.28kg of aluminum dihydrogen phosphate for mixing, and press into block chrome corundum.
[0060] Step 3: sinter the pressed block chrome corundum in a high temperature furnace at 1400° C. for 24 hours to obtain chrome corundum refractory bricks.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 1 is that step 2 is: adding 25kg of fused zirconium mullite with a particle size of 2mm, 4kg of nano hexagonal boron nitride and 2kg of nano silicon dioxide to the detoxified chrome corundum, and then adding 3.125kg of phosphoric acid, stirring evenly and leaving for 6h, and then adding 1.28kg of aluminum dihydrogen phosphate for mixing, and pressing to form block chrome corundum. The remaining steps are consistent with the example.
[0063] The refractory bricks prepared in Examples 1 to 5 and Comparative Example 1 were tested for corrosion resistance, and the method was as follows: the sampled bricks were immersed in a 10% hydrogen chloride solution, a 10% sodium hydroxide solution, a 10% sodium chloride solution, and a 10% sodium sulfate solution, respectively, for 8 months. After being taken out, their strength was tested, and the corrosion coefficient = the strength of the brick after corrosion / the strength of the brick immersed in water at the same age. The test results are shown in Table 1.
[0064] Table 1
[0065]
[0066] As can be seen from Table 1, in Example 4, the corrosion resistance of the detoxified chrome corundum is improved by surface nickel plating of the detoxified chrome corundum, and the corrosion resistance of the refractory bricks finally prepared is improved compared with Examples 1 to 3. In Example 5, nano hexagonal boron nitride and nano silicon dioxide are additionally added on the basis of Example 4 to further improve the overall corrosion resistance of the refractory bricks. The corrosion resistance of the refractory bricks finally prepared is significantly improved compared with Examples 1 to 3. In Comparative Example 1, only nano hexagonal boron nitride and nano silicon dioxide are additionally added, which also improves the corrosion resistance of the refractory bricks, but the effect is not significant.
[0067] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for detoxifying chrome corundum and producing refractory bricks, characterized in that: The following steps are involved: Step 1, crushing the chrome corundum into different specifications, then placing it in a leaching solution to leach free hexavalent chromium, and then filtering, washing, and drying the soaked chrome corundum to obtain detoxified chrome corundum; Step 2: adding fused zirconium mullite and a binder of phosphoric acid to the detoxified chrome corundum, stirring and mixing, leaving for a period of time, adding a binder of aluminum dihydrogen phosphate, mixing, and pressing to form a block of chrome corundum; Step 3: Sintering the pressed block of chrome corundum at high temperature to obtain chrome corundum refractory bricks.
2. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: In the step 1, the chromium corundum is crushed to a particle size of 1 to 5 mm or 100 to 400 meshes.
3. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: In the step 1, the leaching solution is one of a reducing agent, water or an acid. The reducing agent can be hydrazine hydrate, and the acid can be one or more of nitric acid, hydrochloric acid and sulfuric acid.
4. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: In the step 1, the leaching process is: taking a reducing agent or water or acid at room temperature, adding chrome corundum thereto at a mass ratio of 1:1, and leaving it for 24 hours to leach free hexavalent chromium.
5. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: In the step 2, the mass ratio of chrome corundum to fused zirconium mullite is 4-16:1, and the amount of phosphoric acid added as a binder is 2.5%-5% of the total mass of the chrome corundum and the fused zirconium mullite.
6. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: In the step 2, the particle size of the fused zirconium mullite is 0 to 3 mm.
7. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: In the step 3, the amount of aluminum dihydrogen phosphate added as a binder is 1% to 2.5% of the total mass of chrome corundum, fused zirconium mullite and binder phosphoric acid.
8. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: In the step three, the high temperature sintering temperature is 1400° C. to 1600° C., and the sintering time is 20 h to 25 h.
9. The method for detoxifying chrome corundum and producing refractory bricks according to claim 1, characterized in that: Before step 2, the detoxified chrome corundum is first modified by: S1. Immerse the detoxified chrome corundum in a mixed acid of 3% nitric acid and 2% hydrofluoric acid, soak it at 15-30°C for 5-10 minutes, then take out the detoxified chrome corundum, wash it, and dry it; S2, soaking the dried detoxified chrome corundum in 40g / L tin chloride acid solution at room temperature for 8-16min, then taking out the detoxified chrome corundum, placing it in an acetone solution for ultrasonic cleaning, and drying; S3, soaking the dried detoxification chrome corundum in 0.15g / L palladium chloride acid solution, soaking at 40-50°C for 8-16min, then taking out the detoxification chrome corundum, washing and drying; S4. Soak the dried detoxified chrome corundum in a chemical plating solution, which includes 8g / L NiSO4, 30g / L, 15g / L CH3COONa, 25g / L sodium citrate, and 8ml / L lactic acid. Soak the solution at 80-90°C for 30-45min. After soaking, take it out to obtain modified detoxified chrome corundum with nickel plating on the surface.
10. The method for detoxifying chrome corundum and producing refractory bricks according to claim 9, characterized in that: After the detoxified chromium corundum is modified, 4-6% of the mass of the detoxified chromium corundum is additionally added with nano hexagonal boron nitride and nano silicon dioxide in step 2, and the mass ratio of the nano hexagonal boron nitride to the nano silicon dioxide is 2:1.
Citation Information
Patent Citations
High-corrosion-resistance composite ceramic material
CN104150907A
Method for producing large-scale copper smelting furnace lining bricks by smelting chromium slag
CN105777159A
Preparation method for zirconia alumina and high chromium cast iron composite material
CN107541656A
Production method for compression resistant mold
CN107973585A
Production method of chromium corundum brick with reduction reaction resistance and thermal shock resistance for non-ferrous metal smelting fuming furnace or side-blown furnace
CN111423222A